EFFECTIVENESS OF SPECIES, THICKNESS, AND AGE OF LEAVES ON THE PERFORMANCE OF ORNAMENTAL PALM FIBER AS A CARBON MONOXIDE BIOFILTER IN FOREST FIRE SMOKE - Eva Gusmira; Nissa Sukmawati; Reni Kartika; Habibillah Alva Putra (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2026)
Carbon monoxide (CO) emitted from forest fire smoke requires low-cost and environmentally friendly filtration methods. This study evaluated the effects of palm species, filter thickness, and leaf age on the performance of ornamental palm leaf fiber biofilters for CO reduction. Three palm species Veitchia merrillii, Wodyetia bifurcata, and Cyrtostachys renda were tested using mature and young leaves. Palm leaf fibers were processed into filter sheets with thicknesses of 0.3, 0.5, and 0.7 mm. CO concentrations were measured before and after filtration, and filter effectiveness was calculated as the percentage reduction in CO concentration. Pore-size distribution was analyzed using a trinocular microscope and Examet software. The highest effectiveness for mature leaves was obtained from Wodyetia bifurcata at 0.5 mm thickness, with a CO reduction of 49.11%, whereas the highest effectiveness for young leaves was obtained from Veitchia merrillii at 0.7 mm thickness, with a CO reduction of 57.39%. Increasing filter thickness did not produce a uniform response; the effect varied depending on palm species and leaf age. These findings indicate the preliminary potential of ornamental palm leaf fibers as low-cost, biomass-based filter materials for laboratory-scale CO reduction. The novelty of this study lies in evaluating processed ornamental palm leaf fibers as CO biofilter media by comparing palm species, leaf age, and filter thickness. However, this study was limited by the absence of replicated measurements, adsorption-capacity testing, airflow-resistance measurement, and long-term durability evaluation.